An organic-inorganic ceramic composite membrane, preparation method and application thereof in zinc-based liquid flow battery

By spin-coating an ultra-thin hydrophilic organic polymer layer on the surface of the inorganic porous ceramic membrane, an organic-inorganic ceramic composite film is formed, which solves the problem of zinc dendrites piercing the separator in zinc-based liquid flow batteries, and realizes the ultra-long battery Cycling stability and high area capacity and reduce costs.

CN116093366BActive Publication Date: 2025-02-07NANJING TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210527879.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-16
Publication Date
2025-02-07
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

Existing zinc-based flow batteries face the problem of zinc dendrites piercing the diaphragm, resulting in poor battery stability and low area and capacity, which limits its development.

Method used

Using an organic-inorganic ceramic composite film, an ultra-thin hydrophilic organic polymer layer is spin-coated on the surface of the inorganic porous ceramic film to form a composite film. The composite film combines the mechanical strength of the ceramic film and the high ion selectivity of the organic layer, which can effectively resist zinc dendrites puncture and increase the zinc deposition site of zincate ions.

Benefits of technology

The ultra-long cycle stability and high area capacity of zinc-based flow batteries are achieved, which significantly improves the performance and life of the battery, and at the same time reduces the cost through the recycling of ceramic membranes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116093366B_ABST
    Figure CN116093366B_ABST
Patent Text Reader

Abstract

The present invention discloses an organic-inorganic ceramic composite membrane, a preparation method and its application in a zinc-based liquid flow battery. The inorganic porous ceramic membrane with ultra-high mechanical strength is used as a substrate, and an ultra-thin organic polymer layer is covered on its surface to prepare the composite membrane. The organic-inorganic ceramic composite membrane of the present invention has an asymmetric structure up and down. The ultra-high mechanical strength of the bottom ceramic membrane can effectively resist the penetration of zinc dendrites; and its larger porosity can be used to provide more zinc deposition space for zincate to achieve ultra-high area capacity; the ultra-thin organic polymer layer on the surface effectively reduces the surface pore size of the inorganic porous ceramic membrane to achieve high ion selectivity, and its application in zinc-based liquid flow batteries shows excellent battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of liquid flow batteries, and in particular relates to an organic-inorganic ceramic composite membrane, a preparation method and application thereof. Background Art

[0002] With the increasing energy crisis and environmental pollution, green energy such as solar energy, wind energy and tidal energy has attracted widespread attention. However, due to differences in regions and time zones, there will be certain fluctuations and intermittentity when using wind energy, solar energy and other energy sources to generate electricity, so a certain energy storage system is needed to balance the electricity. Among the many energy conversion and storage systems, zinc-based flow batteries (ZFBs) have good prospects in the field of redox flow batteries due to their low cost, high safety and environmental friendliness, and have received widespread attention from researchers. However, zinc dendrites will pierce the battery separator and cause the battery to short-circuit, so zinc dendrites are the key factor affecting the stability of ZFBs and restricting its development; and ZFBs also face the problem of low area capacity. Improving the battery area capacity can be done from two aspects: one is to increase the electrode porosity, and the other is to increase the effective contact area of ​​the battery separator to provide more deposition sites for elemental zinc. Therefore, researchers are currently committed to exploring porous membrane materials that can resist zinc dendrites and have a large effective contact area.

[0003] Recently, Yuan et al. proposed to use PES porous membrane as the substrate and introduce sulfonated polyetheretherketone (SPEEK) into the membrane. According to the Donnan effect, zinc was induced to deposit on carbon felt, which significantly improved the cycle life of alkaline zinc-iron flow battery (AZIFB). Wu et al. designed a special membrane morphology - Turing membrane, which increased the effective area of ​​the membrane by using peaks and valleys to provide a large amount of zinc deposition space for zincate ions, and introduced Cu 2+ Inducing uniform zinc deposition, thus achieving high area capacity of AZIFB. However, these modification methods still cannot change the final zinc dendrite piercing the separator, thus causing a sharp decline in battery performance. In summary, improving the mechanical properties of the membrane is the fundamental way to prevent zinc dendrites from piercing the battery separator.

[0004] References:

[0005] (1) Yuan, Z. et al. Negatively charged nanoporous membrane for adendrite-free alkaline zinc-based flow battery with long cycle life. NatCommun 9,3731;

[0006] (2)Wu,J.et al.Dendrite-Free Zinc-Based Battery with High ArealCapacity via the Region-Induced Deposition Effect of Turing Membrane.J AmChem Soc 143,13135-13144. Summary of the invention

[0007] In order to address the deficiencies of the prior art, the purpose of the present invention is to provide an organic-inorganic ceramic composite membrane that can effectively resist zinc dendrites from piercing the diaphragm, achieve ultra-long cycle stability of zinc-based liquid flow batteries, and provide more zinc deposition sites for zincate ions to increase the area capacity of zinc-based liquid flow batteries.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] An organic-inorganic ceramic composite membrane comprises a substrate and a surface layer covering the surface of the substrate, wherein the substrate is an inorganic porous ceramic membrane and the surface layer is made of a hydrophilic organic polymer material.

[0010] Preferably, the inorganic porous ceramic membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon carbide, and has a thickness of 0.5 to 2 mm and a pore size of 50 to 200 nm.

[0011] Preferably, the organic polymer is one or more of polysulfones, polyketones, polyimide, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, polybenzimidazole, polyvinyl pyridine, polyethylene, polypropylene, chitosan or cellulose acetate, and has a thickness of 30 to 50 nm.

[0012] Preferably, the ratio of the mass of the aforementioned organic polymer to the surface area of ​​the inorganic porous ceramic membrane is 0.001 to 0.003 g·cm-2.

[0013] A method for preparing an organic-inorganic ceramic composite film comprises the following specific steps:

[0014] S1, dispersing the organic polymer in the organic solvent and stirring to form a uniform film casting solution;

[0015] S2. Covering the casting liquid on the surface of the inorganic porous ceramic membrane in batches and drying it to obtain an organic-inorganic ceramic composite membrane.

[0016] Preferably, in the aforementioned step S1, the organic solvent is selected from one or more of N-dimethylformamide, N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; the volume ratio of the mass of the organic polymer to the organic solvent in the casting solution is 0.5-2 g / 10 mL; in step S2, the covering method is spin coating or dipping, 200-500 μL is spin coated each time, and the spin coating is 2-6 times; the drying process is vacuum drying, the drying temperature is 60-150°C, and the drying time is 8-24 h.

[0017] Application of an organic-inorganic ceramic composite membrane in zinc-based liquid flow batteries.

[0018] The method for recovering the inorganic ceramic composite membrane in the aforementioned application comprises the following steps: cleaning the organic-inorganic ceramic composite membrane after ultra-long cycles in the zinc-based liquid flow battery in a cleaning solvent, calcining, and recovering the inorganic porous ceramic membrane.

[0019] Preferably, the cleaning solvent includes cleaning solvent I and cleaning solvent II, cleaning solvent I is 0.1-3M sulfuric acid, and the cleaning time is 5-12 hours; cleaning solvent II is deionized water, and the cleaning time is 24-36 hours; the calcination temperature is 600-800°C, and the calcination time is 7-12 hours.

[0020] Recycled inorganic ceramic composite membranes for the preparation of organic-inorganic ceramic composite membranes and their application in zinc-based flow batteries.

[0021] The present invention is beneficial in that:

[0022] (1) The present invention prepares an organic-inorganic ceramic composite membrane with an inorganic porous ceramic membrane as a substrate by a spin coating method. The excellent mechanical stability of the inorganic porous ceramic membrane can effectively prevent zinc dendrites from piercing the diaphragm, thereby achieving ultra-long cycle stability of the zinc-based liquid flow battery;

[0023] (2) Spin coating an ultra-thin organic polymer layer on the surface of the inorganic porous ceramic membrane can effectively reduce the surface pore size of the inorganic porous ceramic membrane and improve the ion selectivity. The organic polymer layer is hydrophilic, making the organic-inorganic ceramic composite membrane have a higher OH - Ion transmission rate, while taking advantage of the higher porosity of the inorganic porous ceramic membrane, when the inorganic porous ceramic membrane side of the organic-inorganic ceramic composite membrane is facing the negative electrode, it can provide more zinc deposition sites for zincate ions, thereby increasing the area capacity of the zinc-based liquid flow battery;

[0024] (3) When the surface organic polymer layer of the organic-inorganic ceramic membrane is destroyed after an extremely long cycle in the battery, the surface organic polymer layer can be removed by utilizing the excellent thermal stability of the inorganic porous ceramic membrane, thereby realizing the recycling of the inorganic porous ceramic membrane and saving the cost of using ion exchange membranes in liquid flow batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM images of the upper surfaces of alumina porous ceramic membrane (a-CM) and OICCM: (a) a-CM; (b) OICCM;

[0026] Figure 2 The cross-sectional scanning electron microscope (SEM) characterization images of a-CM and organic-inorganic ceramic composite membrane (OICCM): (a) a-CM; (b) OICCM;

[0027] Figure 3 It is Fe(CN)6 4- Permeability curve;

[0028] Figure 4 It is the different ion permeability curves of a-CM and OICCM;

[0029] Figure 5 Yes OH - Permeability curve;

[0030] Figure 6 is the ionic conductivity curve;

[0031] Figure 7 This is a performance comparison chart of OICCM spin-coated with different masses of SPEEK in alkaline zinc-iron flow batteries;

[0032] Figure 8 The optimal SPEEK spin coating volume for OICCM with a-CM and Nafion212 cells at 80 mA cm -2 Long cycle performance graph;

[0033] Fig. 9 is the nanoindentation test result;

[0034] Fig.10 is the SEM characterization of the lower surface of a-CM;

[0035] Fig.11 When OICCM is placed with the ceramic membrane facing the zinc anode, the battery has a high area capacity of 80 mA cm -2 Long cycle performance graph;

[0036] Fig.12 This is the morphology of zinc deposition in the pores when the OICCM is charged to 70% capacity without discharge;

[0037] Fig.13 When OICCM places the SPEEK layer toward the zinc anode, the battery has a high area capacity of 80 mA cm -2 Long cycle performance graph;

[0038] Fig.14It is the surface morphology of the SPEEK layer towards the high surface capacity of the zinc negative electrode after cycling;

[0039] Fig.15 is a graph of the battery performance of OICCM prepared using recycled a-CM. DETAILED DESCRIPTION

[0040] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0041] Example 1

[0042] A method for preparing an organic-inorganic ceramic composite film comprises the following specific steps:

[0043] S0, sulfonating PEEK in sulfuric acid (98 wt.%) at 50° C. for 6 h to prepare sulfonated polyetheretherketone (SPEEK);

[0044] S1. Disperse SPEEK in N-N dimethylformamide (DMF), with the mass ratio of SPEEK to DMF being 1 g / 10 mL, and stir to form a uniform film casting solution;

[0045] S2. Fix the porous alumina ceramic membrane on a spin coater, use a pipette to transfer 500 μL each time, and transfer a total of 2 mL of the casting liquid to the surface of the alumina ceramic membrane with an average pore size of 100 nm. The rotation speed of the spin coater is 3000 rpm for 60 seconds. After the spin coating is completed, place the composite membrane in an oven at 60-80°C and dry it for 12 hours to obtain an organic-inorganic ceramic composite membrane.

[0046] Comparative Example

[0047] The difference from Example 1 is that the casting liquid is not applied to the surface of the alumina ceramic, but directly applied to the glass plate, and then heat-treated and peeled off in the same way to obtain a diaphragm.

[0048] Test Method

[0049] (1)Fe(CN)6 4- Ion permeability

[0050] The effective area is 1.77cm 2The H-type was tested in a diffusion cell. The left diffusion cell was filled with 50mL of 0.4M K4Fe(CN)6+3.0M NaOH solution, and the right diffusion cell was filled with the same volume of 0.4M MgSO4+3.0M NaOH solution to balance the ionic strength and osmotic pressure, and magnetic stirring was used to reduce concentration polarization during the test. 4mL of the solution was taken from the right diffusion cell at intervals, and 4mL of 0.4M MgSO4+3.0M NaOH was immediately added to the right diffusion cell, and the absorbance was measured at 323.5nm using a UV-visible spectrophotometer. The standard absorbance / concentration curve was used to determine the concentration of Fe(CN)6 4- The concentration of Fe(CN)6 4- The permeability can be calculated using the following formula:

[0051]

[0052] Where V B is the volume of MgSO4 / NaOH solution, which is 50ml in this experiment; C B (t) is the Fe(CN)6 in MgSO4 / NaOH solution at time t 4- The concentration of ions; C A is Fe(CN)6 in K4Fe(CN)6 / NaOH solution 4- concentration, can be considered as a constant to simplify the calculation if the test time is not too long; A and L are the effective membrane area and membrane thickness respectively; P is Fe(CN)6 4- The penetration rate of ions.

[0053] (2) OH - Ion permeability

[0054] The effective area is 1.77cm 2 The H-type diffusion cell was tested, with 50 mL of 5M NaOH solution in the left diffusion cell and 50 mL of deionized water in the right diffusion cell. The hydroxide ion concentration in the right half of the cell with different diffusion times was measured by a pH meter.

[0055] (3) Different ion permeability

[0056] The effective area is 1.77cm 2 The H-type diffusion cell was tested. The left diffusion cell contained 50 mL of 1M KCl / NaCl / MgCl2 / LiCl / K3Fe(CN)6 solution, and the right diffusion cell contained 50 mL of ultrapure water. The conductivity meter was used to test the ionic conductivity in the right half of the cell at different diffusion times.

[0057] (4) Single cell performance

[0058] The performance of the zinc-iron flow battery was tested using a homemade flow battery system, which consists of an organic-inorganic ceramic membrane, two carbon felt electrodes, two graphite plate current collectors and a pair of shells. The membrane separates the positive electrolyte (8ml 0.6MK4Fe(CN)6+5MNaOH) and the negative electrolyte (8ml 0.3M ZnO+5M NaOH) and is sandwiched between the two electrodes. For the charge and discharge tests, the charge capacity was 70% of the theoretical capacity, the discharge cutoff voltage was 0.1V, and the variable current density test range was 40-240mA·cm -2 ; Constant current density is 80mA·cm -2 Tested under the same conditions; high area capacity test battery performance The volume of the positive and negative electrolytes was 60mL and 80mL, and the area capacities were calculated to be 172mAh·cm based on the membrane area. -2 、243mAh·cm -2 , the test current density is still 80mA·cm -2 During the test, nitrogen protection was used. The coulombic efficiency (CE), voltage efficiency (VE) and energy efficiency (EE) of the battery were calculated by the following formula:

[0059]

[0060]

[0061]

[0062] Where Cd and Cc are the discharge capacity and charge capacity respectively; Ed and Ec are the discharge energy and charge energy respectively.

[0063] Test Results

[0064] (1) Characterization of organic-inorganic ceramic composite membranes

[0065] like Figure 1 As shown in Figure 2, compared with the alumina ceramic membrane, the surface pores of the organic-inorganic ceramic composite membrane (OICCM) are almost completely covered by organic polymers, which effectively reduces the pore size; and the surface layer of the OICCM is an ultra-thin SPEEK organic layer, as shown in Figure 2. Figure 2 .

[0066] (2) Ion permeability and ion conductivity of organic-inorganic ceramic composite membranes

[0067] In liquid flow batteries, ion exchange membranes are required to have high ion selectivity. The presence of an ultra-thin SPEEK organic layer on the surface of OICCM is beneficial to improving ion selectivity. According to Fe(CN)6 4- The results of ion penetration show that ( Figure 3 ): OICCM inhibits Fe(CN)64- The ion permeation capacity is significantly higher than that of alumina ceramic membranes, and is comparable to that of commercial Nafion membranes in inhibiting Fe(CN)6 4- The ion permeation ability is basically the same, and the selectivity of OICCM for different ions is significantly improved compared with alumina ceramic membrane due to the presence of ultra-thin organic layer on the surface ( Figure 4 ), OICCM ion selectivity (K+ / Fe(CN)6 3- =58.91) is an alumina ceramic membrane (K+ / Fe(CN)6 3- =6.79), which is beneficial to improve the effective ion transport while inhibiting the cross-talk of active substances in the electrolyte. At the same time, OICCM also has a higher OH - Ion permeability ( Figure 5 ) and ionic conductivity ( Figure 6 ).

[0068] (3) Effect of the amount of sulfonated polyetheretherketone spin coating

[0069] When the amount of SPPEK spin coating is high, the ability to inhibit the penetration of active substances will increase, thereby improving the coulombic efficiency of alkaline zinc-iron batteries; however, as the amount of spin coating increases, the internal resistance of the membrane will increase, thereby reducing the voltage efficiency of alkaline zinc-iron flow batteries ( Figure 7 ), according to the trade-off effect, the optimal SPEEK coating amount range is 0.0015-0.003g / cm 2 Because OICCM has a higher mechanical strength than organic membranes ( Figure 8 ), which is sufficient to resist the penetration of zinc dendrites, and OICCM can effectively inhibit the Fe(CN)6 4- Ion permeation, so its 80mA·cm in zinc-iron flow battery -2 During the test, it can stably cycle 1000 times ( Fig. 9 );CM because Fe(CN)6 4- The ion penetration is serious and therefore cannot be stably cycled; while the commercial Nafion 212 was pierced by zinc dendrites after only 60 cycles.

[0070] (4) Effect of organic-inorganic ceramic composite membrane on battery area capacity

[0071] The lower surface of OICCM is an alumina ceramic membrane with larger pores ( Fig.10), using the large porosity and excellent mechanical strength of alumina ceramic membrane, the lower surface of OICCM is facing the zinc negative electrode of the alkaline zinc-iron flow battery, which can provide more zinc deposition sites for zincate ions to achieve high area capacity, and can resist zinc dendrite puncture to achieve long cycle stability. The application of OICCM in alkaline zinc-iron flow batteries can maintain high area capacity and stable cycle for 1000h ( Fig.11 ), when OICCM was charged to 70% without discharge in an alkaline zinc-iron flow battery, zinc deposition was indeed present in the side pores of the alumina ceramic membrane, further confirming that the ceramic membrane pores provide more zinc deposition sites for zincate ( Fig.12 In order to further prove that the ceramic membrane pores are conducive to zinc deposition, the SPEEK membrane layer in OICCM was placed toward the zinc negative electrode to test its long-term cycle stability at high area capacity. It was found that the composite membrane could only stably cycle for 50 hours, and the battery CE dropped significantly ( Fig.13 ), SEM characterization of OICCM revealed that its surface was obviously damaged ( Fig.14 ), which once again proves that the pores of ceramic membranes are beneficial to improving the battery area capacity.

[0072] (5) Recycling performance of organic-inorganic ceramic composite membranes

[0073] The excellent thermal stability of alumina ceramic membranes can be used to achieve their reuse to save costs. After the OICCM is cleaned after cycling in an alkaline zinc-iron flow battery and calcined in a muffle furnace to burn off the surface SPEEK organic layer, the resulting alumina ceramic membrane is re-spin-coated to obtain a new OICCM and applied to an alkaline zinc-iron flow battery, which can still maintain a high battery cycle performance ( Fig.15 ).

[0074] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the above embodiments do not limit the present invention in any form, and any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. Application of an organic-inorganic ceramic composite membrane in a zinc-based liquid flow battery, characterized in that: The organic-inorganic ceramic composite membrane is used as a battery separator, including a substrate and a surface layer covering the surface of the substrate, wherein the substrate is an inorganic porous ceramic membrane, the inorganic porous ceramic membrane faces the negative electrode side of the battery, the surface layer is made of a hydrophilic organic polymer material, the inorganic porous ceramic membrane has a thickness of 0.5-2 mm, a pore size of 50-200 nm, a thickness of 30-50 nm, and a mass ratio of the hydrophilic organic polymer material to the surface area of ​​the inorganic porous ceramic membrane of 0.001-0.003 g•cm -2 ; The inorganic porous ceramic membrane recovery method comprises the following steps: cleaning the organic-inorganic ceramic composite membrane after ultra-long cycles in a zinc-based liquid flow battery in a cleaning solvent, calcining, and recovering the inorganic porous ceramic membrane.

2. The use according to claim 1, characterized in that: The material of the inorganic porous ceramic membrane is one of aluminum oxide, zirconium oxide, titanium oxide or silicon carbide.

3. The use according to claim 1, characterized in that: The hydrophilic organic polymer material is one or more of polyketones, polyvinylidene fluoride, polybenzimidazole, polyvinyl pyridine, chitosan or cellulose acetate.

4. The use according to claim 1, characterized in that: The method for preparing the organic-inorganic ceramic composite film comprises the following specific steps: S1, dispersing the organic polymer in the organic solvent and stirring to form a uniform film casting solution; S2. Covering the casting liquid on the surface of the inorganic porous ceramic membrane in batches and drying it to obtain an organic-inorganic ceramic composite membrane.

5. The use according to claim 4, characterized in that: In the step S1, the organic solvent is selected from one or more of N-dimethylformamide, N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone; the volume ratio of the organic polymer mass to the organic solvent in the casting solution is 0.5-2 g / 10 mL; in the step S2, the covering method is a spin coating method or a dipping method.

6. The use according to claim 1, characterized in that: The cleaning solvent includes cleaning solvent I and cleaning solvent II, the cleaning solvent I is 0.1~3M sulfuric acid, and the cleaning time is 5~12h; the cleaning solvent II is deionized water, and the cleaning time is 24~36h; the calcination temperature is 600~800℃, and the calcination time is 7~12h.

Citation Information

Patent Citations

  • Water system zinc ion battery composite diaphragm and preparation method thereof

    CN110364660A